PERBEDAAN KEMAMPUAN PEMAHAMAN KONSEP MATEMATIKA MELALUI PENERAPAN MODEL PEMBELAJARAN STUDENT TEAMS ACHIEVEMENT DIVISION DENGAN TEAMS GAME TOURNAMENT PADA MATA PELAJARAN MATEMATIKA - Zenal Abidin; Yennie Widyaningsih (Bale Aksara: Jurnal Pendidikan Sekolah Dasar, 2020)
One of the goals of learning mathematics is to develop abilities understanding of mathematical concepts. One component of learning that can be affect the learning process of understanding mathematical concepts students are a learning model. Learning model is a way which is designed for the implementation of learning. Meanwhile, this research discuss the differences in the ability to understand mathematical concepts through the application of the learning models for student teams achievement division with teams game tournaments on math. Aim This research is to find out the ability to understand mathematical concepts among students who get the Student type cooperative learning model Teams Achievement Division and Teams Game Tournament . Research methods The method used in this research is the quantitative method of experimentation, as for The experiments used are Quasi Experiments with shapes Nonequivalent control group design . The population in this study is all Grade V students of SDN 4 Tanjungkamuning totaling 36 students. Inside sample This research is VA and VB grade students at SDN 4 Tanjungkamuning yang totaling 36 students. The sampling technique used is a technique saturated sampling. The instruments used in this study are description tests, and observation sheets. The results showed there were differences in the ability of understanding mathematical concepts between students who are get the cooperative learning model type Student Teams AchievementDivisionwithstudentswhogettheTeamsGameTournamentmodel.Based on the results of data analysis on the pretest and posttest value of experimental class I with an average pretest of 5.28 and an average posttest of 10. Meanwhile, in class Experiment II showed a pretest value of 3.89 and an average posttest of 7.61. Based on the two data shows that the experimental class I is average the value is higher than the average of the experimental class II . This research shows that the results of the analysis of experimental class I data using the Student model Teams Achievement Division averages higher than class experiment II using the Teams Game Tournament model. Keywords : Student Teams Achievement Learning Model , Model Learning Division Teams Game Tournament , comprehension ability mathematical concepts.PERBEDAAN KEMAMPUAN PEMAHAMAN KONSEP MATEMATIKA MELALUI PENERAPAN MODEL PEMBELAJARAN STUDENT TEAMS ACHIEVEMENT DIVISION DENGAN TEAMS GAME TOURNAMENT PADA MATA PELAJARAN MATEMATIKA